AN ASSESSMENT OF THE IMPLEMENTATION OF PRIMARY HEALTHCARE PROGRAMMES IN LOKOJA LOCAL GOVERNMENT AREA OF KOGI STATE 2016 –2021 - Godsent Okenyi Adaji; E.E. Lawal; Timothy Onimisi (International Studies Journal)
This paper is an assessment of the implementation of Primary Healthcare Programmes in Lokoja Local Government Area of Kogi State. It is a fact that no society can develop without the government providing proper healthcare system for its populace who in turn are expected to contribute to the sustainable political and socio[1]economic development of the nation. This study therefore considered the minimum standards for Primary Healthcare in Nigeria as outlined in the Guidelines Manual prepared by the National Primary Healthcare Development Agency and thereafter, examined the actual implementation of Primary Healthcare Programmes especially in the study area during the period under review. The study is theoretically guided by the David Easton’s System theory to interrogate the intervening variables that shapes the implementation of the policy within the study area. The study relies on secondary sources of data. The findings revealed that the implementation of the policy is shrewded with mixed feelings. Hence, there is a variation from what the minimum standard says and the actual implementation in Lokoja Local Government Area. It is among other things recommended that government at all levels should provide adequate funds and logistics for optimal primary healthcare services at both the urban and rural areas as prescribed by the National Primary Healthcare Development Agency.